Th17/Treg Imbalance in Chronic Obstructive Pulmonary Disease: Clinical and Experimental Evidence - Lourenço, Juliana Dias; Ito, Juliana Tiyaki; Martins, Milton de Arruda; Tibério, Iolanda de Fátima Lopes Calvo; Lopes, Fernanda Degobbi Tenorio Quirino dos Santos (Frontiers in Immunology, 2021)
The imbalance between pro- and anti-inflammatory immune responses mediated by Th17 and Treg cells is deeply involved in the development and progression of inflammation in chronic obstructive pulmonary disease (COPD). Several clinical and experimental studies have described the Th17/Treg imbalance in COPD progression. Due to its importance, many studies have also evaluated the effect of different treatments targeting Th17/Treg cells. However, discrepant results have been observed among different lung compartments, different COPD stages or local and systemic markers. Thus, the data must be carefully examined. In this context, this review explores and summarizes the recent outcomes of Th17/Treg imbalance in COPD development and progression in clinical, experimental and in vitro studies.